Sistem Informasi Monitoring dan Evaluasi Kinerja Service Center Menggunakan Performance Dashboard - Pradana, Kelvin; Utomo, Agus Prasetyo; Mariana, Novita (Jurnal Informatika, 2024)
This research focuses on the development of a performance dashboard application to measure Key Performance Indicators (KPIs) such as the Customer Satisfaction Index (CSI) and Net Promoter Score (NPS). The main issue is the inaccurate measurement of customer satisfaction, making it difficult for management to make the right decisions in designing business strategies. The system development methodology is the Rapid Application Development (RAD) approach, which allows for quick and efficient application development. This system enables the company to effectively monitor and analyze performance data that can aid in better decision-making. With the information provided by this system, the company can adjust its business strategies to improve customer satisfaction, increase loyalty, and achieve its business goals. The research findings show that this dashboard system can provide more accurate insights into customer satisfaction and loyalty, which in turn helps the company improve service performance, address weak areas, and plan more measurable strategic steps to effectively achieve business goals